Tracing Airline Travelers for a Public Health Investigation: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) Infection in the United States, 2014. (July 2016) - Regan, Joanna J.; Jungerman, M. Robynne; Lippold, Susan A.; Washburn, Faith; Roland, Efrosini; Objio, Tina; Schembri, Christopher; Gulati, Reena; Edelson, Paul J.; Alvarado-Ramy, Francisco; Pesik, Nicki; Cohen, Nicole J.
Objective: CDC routinely conducts contact investigations involving travelers on commercial conveyances, such as aircrafts, cargo vessels, and cruise ships. Methods: The agency used established systems of communication and partnerships with other federal agencies to quickly provide accurate traveler contact information to states and jurisdictions to alert contacts of potential exposure to two travelers with Middle East Respiratory Syndrome Coronavirus (MERS-CoV) who had entered the United States on commercial flights in April and May 2014. Results: Applying the same process used to trace and notify travelers during routine investigations, such as those for tuberculosis or measles, CDC was able to notify most travelers of their potential exposure to MERS-CoV during the first few days of each investigation. Conclusion: To prevent the introduction and spread of newly emerging infectious diseases, travelers need to be located and contacted quickly.